The Monkeypox Pandemic as a Worldwide Emergence: Much Ado? - Massimo Ciccozzi; Nicola Petrosillo (MDPI AG, 2022)
The dramatic emergence of SARS-CoV-2 infection worldwide opened the Pandora's box of fears and frights for new emerging infections [...]